S118 Chronic thromboembolic pulmonary hypertension (CTEPH) – is it chronically underdiagnosed?. (December 2018) - Suntharalingam, J; MacKenzie Ross, R; Robinson, G; Hall, T; Hudson, B; Redman, S; Graham, R; Little, D; Easaw, J; Augustine, D; Carson, K; Coghlan, GJ
Abstract : Introduction: Chronic Thromboembolic Pulmonary Hypertension (CTEPH) is a potentially curable form of Pulmonary Hypertension (PH), thought to develop as a rare complication of acute pulmonary embolic disease. Although treatable, it is estimated that only 7%–29% of cases are diagnosed. This abstract examines the impact of developing a regional specialist PH service within our District General Hospital (DGH) on our local incidence of CTEPH, compared with national figures. Methods: Since 2007 the Royal United Hospital (RUH) Bath has offered a regional shared care PH service to the South West, in collaboration with the Royal Free. The service now involves staff from several specialties within the hospital, increasing local awareness of PH. A retrospective analysis was carried out of all CTEPH patients diagnosed within our local DGH catchment area of 4 50 000 between 2007 and 2018, from which annual incidence figures were calculated. A further analysis was carried out of patients with Chronic Thromboembolic Disease (CTED) ie those with persistent thrombus but no associated PH. Results: 43 local patients (58% male, 60.4 years) were diagnosed with CTEPH between 2007–2018, resulting in an average annual incidence 8.3 cases/million (95% CI 4.8, 11.8) and prevalence 68.9 cases/million. This is higher than UK-wide figures extrapolated from the 2017 National PH audit (annual incidence 4.7 cases/million and prevalence 32 cases/million). Referrals were received from 9 different specialties. Average Pulmonary Vascular Resistance (PVR) at presentation fell over time (R 2 0.3022) (figure 1) suggesting patients diagnosed more recently were picked up at an earlier stage in their disease process. All patients were discussed at the national pulmonary endarterectomy MDT at Papworth. 38/43 received active treatment – 30/43 (70%) had technically operable disease, with 19/30 undergoing surgery, whilst 22/43 received medical therapy, including 3 patients post-surgery. In addition, a further 33 patients were diagnosed with CTED and were managed with anticoagulation alone. During the same timescale the service diagnosed 162 CTEPH and 100 CTED cases from the wider regional catchment area. Conclusions: Developing a specialist PH service has increased our local diagnoses of CTEPH above national rates. The data supports the literature that this potentially treatable condition is currently under-diagnosed.